PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP MOTIVASI BERWIRAUSAHA UNTUK MENUMBUHKAN MINAT BERWIRAUSAHA - heri aryadi (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
According to sociologist David Mc Cleiland, a country said to be a developed country, it takes at least 2% of the population in a country to be an entrepreneur by profession. According to Agus Muharram, based on data from the year 2012 currently the number of entrepreneurs in Indonesia has reached 1.56%. This means that Indonesia is not fulfilling the criteria of a developed country. Therefore, according to Purdi E. Chandra, entrepreneurship education is very important to create new entrepreneurs, so as to accelerate economic growth and can keep pace with other countries.The purpose of this study was to determine the influence of education and training, toward student’s motivation entrepreneurship so that in the end they are interested in entrepreneurship. The research was conducted on the campus of Bina Sarana Informatika Jatiwaringin Jakarta. Data collected through questionnaires to 135 samples / respondents. Data were processed and analyzed using the techniques Structural Equation Modeling (SEM) with AMOS program version 18.The results showed that there is a positive and significant influence of education on entrepreneurship motivation, as well as there is a positive and significant correlation between training toward entrepreneurship motivation and there is a positive and significant correlation between entrepreneurship motivation towards interest in entrepreneurship.Keywords:  Education, Training, Motivation and Interests entrepreneurship.